Hermann Dörries (1895-1977): Patristics during the 'Kirchenkampf' - Dornbusch, Aneke (Studia Patristica. Vol. CXXX - Papers Presented at the Eighteenth International Conference on Patristic Studies Held in Oxford 2019, 2021)
Patristic research in Germany during the 20th century was deeply shaped by the political changes in this country, of which the biggest was of course the rise and fall of National Socialism (1933-1945). The example of the German church historian Hermann Dörries (1895-1977) shows how Patristic research lost its appeal during the Nazi era, when different historic topics became fashionable, because they could be more easily connected to the current political debates. Before 1933, Hermann Dörries was deeply focused on his research on the homilies of Macarius or the Apophthegmata Patrum. His work on these two topics not only decreased between 1933 and the beginning of World War II, but the works he did publish also convey a completely different idea of the purpose and methods of historical research than the publications before and after. The reasons for these extreme changes lay partly in the fact that with the rise of National Socialism new (pseudo-)historical debates had emerged, for example the question of the compatibility of a Germanic and Christian heritage. But it was not public pressure that led Dörries to partially give up his research and turn to these new questions but rather his personal conviction that it was his duty to engage in these debates and refute false opinions. The example of Hermann Dörries shows how the research of a young, seemingly focused scholar was driven into new and unexpected directions after 1933 and how his work – even after 1945 – was shaped by the political situation he found himself in.